Trends in overweight and obesity over 22 years in a large adult population: the HUNT Study, Norway. Issue 1 (19th March 2013) - Midthjell, K.; Lee, C. M. Y.; Langhammer, A.; Krokstad, S.; Holmen, T. L.; Hveem, K.; Colagiuri, S.; Holmen, J.
Summary Some reports indicate that the obesity epidemic may be slowing down or halting. We followed body mass index (BMI) and waist circumference (WC) in a large adult population in Norway (n = 90 000) from 1984–1986 (HUNT1) through 1995–1997 (HUNT2) to 2006–2008 (HUNT3) to study whether this is occurring in Norway. Height and weight were measured with standardized and identical methods in all three surveys; WC was also measured in HUNT2 and HUNT3. In the three surveys, mean BMI increased from 25.3 to 26.5 and 27.5 kg m−2 in men and from 25.1 to 26.2 and 26.9 kg m−2 in women. Increase in prevalence of obesity (BMI ≥ 30 kg m−2) was greater in men (from 7.7 to 14.4 and 22.1%) compared with women (from 13.3 to 18.3 and 23.1%). In contrast, women had a greater increase in abdominal obesity (WC ≥ 102 cm for men and WC ≥ 88 cm for women). There was a continuous shift in the distribution curve of BMI and WC to the right, demonstrating that the increase in body weight was occurring in all weight groups, but the increase of obesity was greatest in the youngest age groups. Our data showed no signs of a halt in the increase of obesity in this representative Norwegian population.